Desenvolvimento de um novo hidrogel para a regeneração da pele - Miguel, Sónia Alexandra Pereira (2016)
Skin lesions are traumatic events that lead to increased fluid loss, infections, scars formation and the appearance of immunocompromised regions. The loss of skin integrity can result in significant physiological imbalances and disability or even death. Skin functionality must be restored quickly in order to maintain homeostasis. Researchers have been developing new systems to accelerate the healing process. Although the many skin substitutes available in the market, there is none that promotes full restoration of the native structure of skin. Among the various materials used to cover the wound immediately after injury, hydrogels are the most studied. The hydrogels are made of a highly hydrophilic polymeric network forming a three dimensional structure very similar to the extracellular matrix, that allows cell growth. Moreover, hydrogels are biocompatible, biodegradable and have porous structures that allow cell internalization and proliferation within its structure and promote the diffusion of gases, nutrients and waste products. Currently, new hydrogels that respond to external stimuli such as pH, and temperature have been extensively studied in tissue engineering. Thus, the work plan of this master thesis had as main goal to produce a hydrogel composed of deacetylated chitosan and agarose, formed at body temperature (37°C), in order to verify their applicability in the treatment of wounds. The hydrogel structure was initially characterized by Fourier transform infrared spectroscopy. Its inner and surface morphology was characterized by scanning electron microscopy. Cellular adhesion and internalization into the porous structure of the hydrogel was visualized by confocal and scanning electron microscopy. The cytotoxicity profile of the hydrogel was characterized through cell viability assays, and the results obtained confirmed the biocompatibility of the hydrogel. The antimicrobial activity of the hydrogel was also evaluated and the results showed that the hydrogel inhibits the growth, at the surface, of the most common microorganism in skin infection. The results obtained demonstrated that this 3D network has the suitable properties for improving the healing process of cutaneous wounds.